Management Curriculum and Intelligence Emotional in Improving the Quality of Learning Elementary school - Desiana, Desiana; Patimah, Hj. Siti (Riviera Publishing, 2023)
Good curriculum management will create a conducive learning environment. At the same time, emotional intelligence will help individuals manage their emotions and interact well with others. Researchers concentrated on re-analyzing previous studies published in journals such as Google Scholar, Eric, and Science Direct, Emerald, Sage Journals. 15 Scopus-indexed articles from various countries worldwide have been used as sources of information related to research. Next, researchers used qualitative methods by manually conducting thematic analysis to make research findings relevant to previous studies. Based on a literature review by previous researchers, the results show that